(untitled) (Medical Forum Monthly, 2020)
Objective: To highlight the mechanism of iatrogenic urethral injury, lack of skills in catheterization among junior doctors and prevention strategies for urethral injury. Study Design: Prospective observational analytical cross sectional study. Place and Duration of Study: This study was conducted at the Urology Department of Tertiary Care Teaching Hospital, Dera Ghazi Khan from February 2019 to February 2020. Materials and Methods: We recruited145 male patients referred from emergency& in-patients of this hospital, who had iatrogenic urethral injury due to faulty techniques of insertion or removal of Foley catheter. While the patients who pulled out Foley catheter themselves in altered state of consciousness, <18 years and female patients were excluded. A questionnaire was designed for collecting patient demographics, mechanism of Foley catheter related Urethral injury, setting of incidence of urethral injury, grade of healthcare professional performing catheterization &management of injuries. Results: The ages of the patients ranged from 21 to 80 years, with mean age 64.4 ± 5.2.Out of 145 patients who had iatrogenic urethral injuries related to Foley catheterization,110(76%) patients had urethral injury because of Foley balloon inflation in urethra and in 10 (7%) patients Foley catheter was removed without deflating it’s balloon. Whereas 25(17%) patients had multiple manipulation/attempts of urethral catheterization which lead to injury. Regarding the grade of health care professional. Out of 145 iatrogenic urethral injuries, 77(53%) catheterization was performed by house officers, 53 (37%) catheterization by PGR/MO and 15(10%) by paramedical/nursing staff. The major reasons for catheterization 61(42%) were measurement of urine output followed by catheterization for urinary retention due to enlarged prostate were 54(37%). Conclusion: Urethral catheterization still a dilemma, and associated with iatrogenic urethral injuries which is mostly done by junior doctors explaining their lack of the essential skills and knowledge about technique of catheterization, its removal and penile anatomy. This study highlights the imminent need for more intensive training and better simulation models for UC insertion.